2022
DOI: 10.21203/rs.3.rs-1214484/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is SARS-CoV-2 Omicron (B.1.1.529) variant causing different symptoms?

Abstract: Background: Since preliminary evidence suggests that the new SARS-CoV-2 Omicron (B.1.1.529) variant may cause different symptoms and trigger outbreaks associated with less severe illness compared to previous strains, we conducted and infodemic analysis to verify these suppositions.Methods: We searched Google Trends using the most frequent COVID-19 symptoms, with “United Kingdom” country option and search periods “20-26 December 2020” (predominance of Alpha variant) and “19-25 December 2021” (Omicron prevalence… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Along with the increased number of child hospitalizations, the symptoms observed at COVID-19 onset were somewhat different when subsequently infected by the omicron variant or by the delta and previous variants (12,(25)(26)(27)(28). In Italian children, an analysis of online search trends suggested increased upper respiratory airway symptoms and possibly poorly tolerated fever, whereas dyspnea and anosmia/ageusia seemed less frequent (25). The latter finding could also be an indicator of the younger age of infected children and their inability to report such symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the increased number of child hospitalizations, the symptoms observed at COVID-19 onset were somewhat different when subsequently infected by the omicron variant or by the delta and previous variants (12,(25)(26)(27)(28). In Italian children, an analysis of online search trends suggested increased upper respiratory airway symptoms and possibly poorly tolerated fever, whereas dyspnea and anosmia/ageusia seemed less frequent (25). The latter finding could also be an indicator of the younger age of infected children and their inability to report such symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Chow et al [21], as well as one of the series from the report by McCulloch et al [20], included data from October 2019 to May 2021, while Rogers et al [44] reported on the whole of the winter season in 2019-2020. Nonetheless, even reports more clearly focused on either the pre-pandemic or pandemic timeframe, such as those by Ralli et al [109], Lindner et al [111], Morrone et al [110] and Rogers et al [114], were affected by the various and heterogenous timing of the removal of physical distancing and lockdown, which influenced the circulation of respiratory pathogens, as well as by the emergence of new and more infectious variants of SARS-CoV-2 [123,124].…”
Section: Key Findingsmentioning
confidence: 99%